Flexural and impact properties of poly (vinyl chloride) and acrylic-impact modified poly (vinyl chloride) composite filled with poly (methyl methacrylate) grafted to oil palm empty fruit bunches - Abu Bakar, Aznizam (2012)
Effects of oil palm empty fruit bunch (OPEFB) fiber and OPEFB grafted with poly (methyl methacrylate) on mechanical properties of poly (vinyl chloride) (PVC) and acrylic-impact modified PVC were investigated. The formulations were blended into sheets on a two-roll mill. Test specimens were then hot-pressed. The flexural strength increased, the flexural modulus decreased, and the impact strength relatively constant with the incorporation of grafted fiber. The impact strength of grafted composite improved after acrylic impact modifier (AIM) was added into the grafted composite matrix compared to ungrafted and grafted composite without AIM. The flexural strength and modulus of grafted composite decreased with the addition of AIM.